Competing constraints on Vorfeldbesetzung in German - Speyer, Augustin (ZAS Papers in Linguistics, 2004)
The filling of the 'Vorfeld' in German sentences is basically obligatory; which constituent, however, actually moves to the Vorfeld is underdetermined by syntax and thus governed presumably by discourse factors. Coming from English, there are certain competing expectations one could have: either the topic — more specifically, the backward-looking center — of a sentence is moved to the Vorfeld, or an element in a poset relationship to a set mentioned in the previous discourse, or elements with other functions, such as the exposition of brand-new information or the setting of a scene. A study of a corpus of texts of different stylistic levels showed that indeed all elements expected to appear in the Vorfeld are eligible for Vorfeld-movement, but that there is a strict ranking. Preferred Vorfeld-fillers are phrases containing brand-new information as well as scene-setting elements; only if no such elements are present can elements in a poset relationship with some previously mentioned set be moved to the Vorfeld. Finally, if such elements are not present either, backward-looking centers can move to the Vorfeld. Backward-looking centers have, for this reason, a relatively poor quota among Vorfeld-fillers, namely around 50%.